Znaczenie informacji dotyczących instrumentów finansowych dla użytkowników sprawozdań finansowych - Muszyński, Michał (Value of Information About Financial Instruments for Users of Financial Statements, 2005)
The article shows the rules of financial reporting connected with the financial instruments in the context of the new accounting law and International Accounting Standards. Three key factors connected with financial instruments have been identified, which influence financial statements. These factors are: rules of disclosure of financial instruments in financial statements, valuation of these instruments and supervision of correctness of financial statements made by an auditor.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 339-347